Szkoła Nauk Politycznych Uniwersytetu Jagiellońskiego 1920-1949 - Włodarski, Bartosz (Wydawnictwo Księgarnia Akademicka, 2015)
The Jagiellonian University School of Political Sciences 1920-1949 describes an educational institute established as part of the Jagiellonian University Faculty of Law offering its students two-year supplementary courses in political sciences. The School constituted an essential stage in the history of research and teaching of political sciences at the Jagiellonian University; its academic staff and students created a scientific community of great importance for Cracow and Polish political sciences. The other chapters of the dissertation deal with the history of political sciences at the Jagiellonian University describing professor Michał Rostworowski, the founder and the head of the School of Political Sciences for many years, funding acts, legal system, academic staff, students and their association – the Society of Students and Graduates, syllabus: the system of lectures on international law, policy, economy, and, in detail, lectures on totalitarian ideologies – nazism, fascism and communism in interwar Europe. The last chapter is a summary of the political thought of the main lecturers teaching in the School of Political Sciences. A short period of the School’s activity after the Second World War in the years 1946-1949 is also mentioned there.